Three new species of Laonice (Polychaete: Spionidae) from West and Southwest Africa - Sikorski, Andrey; Pavlova, Lyudmila (Zootaxa, 2016)
Three new species of Laonice (Polychaete: Spionidae): L. galatheae, L. cricketae, L. olgae—are described from South and West Africa (along the coast from 31°14.1ʼS to 04°44ʼN) based on Danish and South African zoological collections. Arguments relative to the morphological heterogeneity of the genus Laonice are advanced. The arguments are based on the following characters: degree of fusion of prostomium with peristomium at the anterior margin, degree of variability of all numerical characters, arrangement of anterior capillaries in two or more vertical rows, presence or absence of transversal dorsal membranous crests in the “post nuchal organ” and presence of genital pouches only on very limited number of segments or other pattern. Authors think it is obvious today an existence of at least four morphologically separate groups of species inside the Laonice-genus: “L. cirrata”, “L. sarsi”, “L. appelloefi” and “L. norgensis” groups. Eight species names from 34 valid names in the genus are still with unclear affiliation. L. quadridentata is treated now as a junior synonym of L. brevicornis. An opinion is expressed about L. insolita not belonging to the genus Laonice because of discrepancy the generic diagnosis.